2008
DOI: 10.1007/s00299-008-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of VvSERK1, VvSERK2, VvSERK3 and VvL1L genes and their expression during somatic embryogenesis of grapevine (Vitis vinifera L.)

Abstract: Little is known about the genes expressed during grapevine somatic embryogenesis. Both groups of Somatic Embryogenesis Receptor Kinase (SERK) and Leafy Cotyledon (LEC and L1L) genes seem to play key roles during somatic embryogenesis in various plant species. Therefore, we identified and analysed the sequences of VvSERK and VvL1L (Leafy cotyledon1-Like) genes. The deduced amino acid sequences of VvSERK1, VvSERK2 and VvSERK3 are very similar to that of registered SERK proteins, with highest homologies for the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 53 publications
4
55
0
2
Order By: Relevance
“…Therefore, PhSERK4 appears to be a marker for normal protocorm development in this orchid. Schellenbaum et al (2008) observed that VvSERK1 and 3 were highly expressed during somatic embryo induction, before the visible appearance of embryos. VvSERK2 appears to be stably expressed and differs from the 2 other VvSERK genes (Schellenbaum et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, PhSERK4 appears to be a marker for normal protocorm development in this orchid. Schellenbaum et al (2008) observed that VvSERK1 and 3 were highly expressed during somatic embryo induction, before the visible appearance of embryos. VvSERK2 appears to be stably expressed and differs from the 2 other VvSERK genes (Schellenbaum et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Schellenbaum et al (2008) observed that VvSERK1 and 3 were highly expressed during somatic embryo induction, before the visible appearance of embryos. VvSERK2 appears to be stably expressed and differs from the 2 other VvSERK genes (Schellenbaum et al, 2008). In wheat, TaSERK1 and 2 transcript levels were enhanced in embryogenic calli and may have a role during somatic embryogenesis, whereas TaSERK3 expression was the highest in developing seeds (Singla et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggestion comes from the fact that LEC1 and L1L were identified before the original Arabidopsis classification and many studies refer to this nomenclature (Zhang et al, 2002;Yazawa et al, 2004;Alemanno et al, 2008;Schellenbaum et al, 2008;Maillot et al, 2009;Salvini et al, 2012). We suggest that reporting on these proteins include mention of the NF-Y names to assist nonexpert readers in understanding the family connection.…”
Section: Classification Nf-ys and Hapsmentioning
confidence: 99%
“…The L1L is crucial for proper embryogenesis performance. Its expression was analyzed during SE induction from singlenode Helianthus annuus (Fambrini et al 2006), Theobroma cacao staminodes (Alemanno et al 2008) as well as the stamen and nodal Vitis vinifera (Schellenbaum et al 2008;Maillot at al. 2009).…”
Section: Introductionmentioning
confidence: 99%